APLIKASI GAME MATEMATIKA DALAM MENINGKATKAN KEMAMPUAN MENGHITUNG MATEMATIS - Dori Lukman Hakim; Rika Mulyati Mustika Sari (Universitas Sultan Ageng Tirtayasa, 2019)
Today's users of gadgets are getting more and more from every year and continuously increasing along with the development of communication information technology. This development has triggered the emergence of various android applications specifically offered to support the sophistication of gadgets, including game applications, business applications, social applications, and educational applications. One android application that has more value is a math game, as if inviting users to play like a game in general but inside it can help develop numeracy skills. In this study, it is very interesting to examine how the application of mathematical games in improving mathematical calculation skills. Most of the gadgets currently used, offer more entertainment, whether it's games or shows that aren't good enough. Therefore the application of this mathematical game application can at least shift the use of the existence of gadgets commonly used for playing or entertainment can be used as a means for learning especially for learning mathematics. This research is an experimental study with a quasi-experimental method that tests a learning with the help of an android math game application through the scientific approach used in the 2013 curriculum. This learning provides a new breakthrough in learning, especially mathematics, because of the presuppositions of learning mathematics it is difficult and scary to switch to being fun and enjoyable with the use of gadgets during the learning process. Keywords: mathematical calculation skills, math game.